2020
DOI: 10.1186/s12991-020-00296-1
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial to assess the effect of Islamic spiritual intervention and of breathing technique with heart rate variability feedback on anxiety, depression and psycho-physiologic coherence in patients after coronary artery bypass surgery

Abstract: Background: This study investigated the effects of Islamic religious and breathing techniques with heart rate variability (HRV) biofeedback therapies on HRV and psycho-physiologic coherence (resonance frequency), depression and anxiety in coronary artery bypass graft surgery (CABG) patients. Methods: Sixty CABG patients were chosen and randomly assigned to religious, breathing techniques and control groups. The experimental groups received 8 weeks of treatments; a 2-h session with home works in each week. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 52 publications
0
20
0
3
Order By: Relevance
“…But the accompanying decreased quality of life and diminished treatment tolerance could worsen course of disease and recovery. Evidence suggests that the presence of anxiety and depression is to be anticipated among patients scheduled for CABG surgery considering the stressors patients undergoing CABG experienced [ 2 , 3 ]. Furthermore, presence of anxiety and depression at the preoperative period triggered psychological responses involving the endocrine and autonomic system, influencing postoperative outcomes and length of stay (LOS) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the accompanying decreased quality of life and diminished treatment tolerance could worsen course of disease and recovery. Evidence suggests that the presence of anxiety and depression is to be anticipated among patients scheduled for CABG surgery considering the stressors patients undergoing CABG experienced [ 2 , 3 ]. Furthermore, presence of anxiety and depression at the preoperative period triggered psychological responses involving the endocrine and autonomic system, influencing postoperative outcomes and length of stay (LOS) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicated that approximately 30 to 40% of CABG surgery patients experienced a form of psychological depression immediately preceding- and post-surgery [ 6 , 7 ]. Patients with high levels of anxiety pre-CABG procedure reported more pain, lesser post-surgery symptom-relief and higher readmissions [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of breathing techniques to control anxiety have been approved in various groups, including, burn patients [10], women with multiple sclerosis [11], obstetrics [12], coronary artery disease [13],…”
Section: Discussionmentioning
confidence: 99%
“…This therapy concurs with the results of the analysis in this review, namely, patients who are undergoing post-cardiac surgery care, i.e., CABG, often experience problems related to psychological and physiological aspects. This review shows that Islamic spiritual healing can help reduce anxiety and become a positive coping in patients with chronic diseases (21). The spiritual therapy in this review is focused on mindfulness-based stress reduction (MBSR).…”
Section: Mind Terapiesmentioning
confidence: 99%